River Cosmology, Social Capital, and Digital Memory: Social Development Strategies of The Riparian Community in Urbanizing Pontianak, West Kalimantan - Annisa Dwi Lestari; Muhammad Maulana; Muhammad Arifin; Putri Rahmah Nur Hakim (Progress In Social Development, 2026)
Riparian communities frequently hold social development assets that are underacknowledged in official policy despite experiencing growing urbanization pressures. These assets are rooted in ecological knowledge, communal solidarity, and cultural practices shaped by long interaction with river environments. This article examines how the Orang Sungai (River People) as Riparian Community in Pontianak, West Kalimantan, Indonesia, sustain community resilience through river cosmology, water-based livelihoods, and digital mnemonic practices. Using a qualitative interpretive approach based on secondary narrative analysis, documentary reading, and contextual digital traces, the article analyzes how river-related meanings, livelihood ethics, and mediated memories support communal life in an urban setting. The analysis argues that river cosmology provides a moral basis for social norms and ecological responsibility. Water-based livelihood practices are converted into economic resilience and social capital within the urban informal economy. Digital mnemonic practices help dispersed community members transmit ecological knowledge and cultural identity across generations. Together, these mechanisms form a bottom-up social development system that operates without formal institutional support. The article also identifies how state empowerment programs may weaken existing community assets through time poverty, elite capture, and participation fatigue. This article contributes to wider debates on riverine communities, local knowledge, social welfare, and participatory development under urban change in the Global South.